Presentation of an Interactive MOOCs Model in the Humanities - Ansarian Tehrani, Azar; Ghaderi, Mostafa; Poushaneh, Kambiz (Iranian Journal of Educational Sociology, 2026)
Purpose: This study aimed to develop and validate a contextually grounded, systematic framework for designing interactive Massive Open Online Courses (MOOCs) tailored to humanities disciplines in Iranian higher education.Methods and Materials: The study employed a sequential exploratory mixed-methods design grounded in a pragmatic paradigm. In the qualitative phase, a systematic review guided by the PRISMA framework was conducted, followed by grounded theory analysis to identify key constructs and their interrelationships. Nineteen higher education experts participated in semi-structured interviews, and thematic analysis was performed using MAXQDA software. The extracted themes were organized into causal conditions, core phenomena, strategies, context, barriers, and consequences. In the quantitative phase, a researcher-developed questionnaire was administered to 272 faculty members in educational management, higher education management, and educational research, selected through multi-stage cluster sampling. Data were analyzed using one-sample t-tests, confirmatory factor analysis, and structural equation modeling with SPSS and SmartPLS software to assess model validity and structural relationships.Findings: The structural equation modeling results indicated statistically significant relationships among the identified constructs. Causal conditions significantly influenced the core phenomenon, which in turn significantly affected strategic dimensions. Strategies demonstrated a strong and significant impact on academic and professional outcomes. Contextual factors and barriers also showed significant effects on strategic implementation. Validation procedures confirmed high internal and external validity of the proposed framework. The model demonstrates that technological infrastructure, instructional content, learner interaction, assessment, and instructional quality collectively contribute to enhanced academic achievement and professional development within humanities-focused interactive MOOCs.Conclusion: The validated framework provides a comprehensive and empirically supported model for the design of interactive MOOCs in the humanities, integrating infrastructural readiness, pedagogical strategy, contextual alignment, and barrier mitigation to enhance academic performance and professional growth in Iranian higher education.